(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Evaluation of field performances and theatrical public holidays in Uzbekistan , scenography art process, spectacle of the scene art processes, about the scientific and theoretical theory of the interdependence of theater and public holidays analyzed .